Laminate
By using a glass substrate, an inorganic film and a specific polyimide resin laminate on the TFT substrate, the problems of heat resistance and yellowness of the polyimide resin at high temperatures are solved, and excellent heat resistance and yellowness are achieved. Low effect, suitable for high-refined displays.
Patent Information
- Application Number
- CN202380041601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-26
- Filing Date
- 2023-05-24
- Publication Date
- 2024-12-31
AI Technical Summary
The existing polyimide resin has excellent heat resistance at high temperatures but has high yellowness, and there is a problem of yellowing of substituents on the aromatic ring, making it difficult to meet the requirements of high-refining and low yellowness such as liquid crystal displays and OLED displays.
Using a glass substrate, an inorganic film and a specific polyimide resin laminate structure, the polyimide resin has a specific structural unit and a high glass transition temperature. By heat treatment above 400°C, it forms excellent heat resistance and yellow color. TFT substrate with low degree.
It realizes a polyimide resin that maintains low yellowness at high temperatures, improves the heat resistance and stability of the TFT substrate, avoids yellowing problems, and is suitable for high-fine display technology.
Smart Images

Figure CN119234485A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate and a method for producing the laminate. Background Art
[0002] Polyimide resins have excellent mechanical properties and heat resistance, and therefore various applications have been studied in the fields of electrical / electronic components, etc. For example, it is expected that glass substrates used in image display devices such as liquid crystal displays and OLED displays will be replaced with polyimide film substrates, and the development of polyimide resins that meet the performance requirements of optical materials is underway.
[0003] Since polyimide resin has excellent properties as described above, development of laminated bodies in which insulating films and conductive films are laminated on polyimide films is underway for electronic devices such as touch sensors and OLEDs.
[0004] For example, Patent Document 1 discloses a method for manufacturing an intermediate material of an electronic component for the purpose of reducing interlayer delamination in a manufacturing process, the method comprising: a process of preparing a supporting substrate formed of glass, a process of forming a first inorganic film containing silicon on one side of the supporting substrate, a process of forming a polyimide film containing fluorine on the first inorganic film, and a process of forming a second inorganic film containing silicon on the polyimide film.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-111010 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] As mentioned above, polyimide resin has excellent properties, but recently further heat resistance is required. For example, in order to achieve high precision of liquid crystal displays and OLED displays, the development of displays with LTPS (low temperature polysilicon TFT) as the device type of TFT is underway. In LTPS displays, the process temperature will reach more than 400°C, and the polyimide used as the substrate is required to have heat resistance that can withstand high temperatures. In addition, with the advancement of display technology, the development of new forms of displays is underway. For example, in transparent displays, displays using UDC (under display camera) technology, etc., the substrate must be required to have low yellowness. Under such circumstances, the aromatic polyimide resin without a substituent of the previously common polyimide has excellent heat resistance at high temperatures, but has a high yellowness problem. In addition, the polyimide with a substituent on the aromatic ring has the problem of easy yellowing. Therefore, a laminate comprising a polyimide with heat resistance and low yellowness is desired.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminate and a production method for a TFT substrate which are excellent in heat resistance, have a low yellowness, and further have a small change in yellowness after heat treatment.
[0011] Solutions for solving problems
[0012] The present inventors have found that the above-mentioned problems can be solved by forming a laminated body in which a glass substrate, an inorganic film, and a specific polyimide resin are laminated, thereby completing the present invention.
[0013] That is, the present invention relates to the following [1] to [9].
[0014] [1] A laminate for use in manufacturing a TFT substrate, comprising: a glass support substrate, a first inorganic film laminated on the support substrate, a polyimide resin laminated on the first inorganic film, and a second inorganic film laminated on the polyimide resin, wherein the polyimide resin has a structural unit of the following general formula (1) or a structural unit of the following general formula (2), and has a glass transition temperature of 400°C or above.
[0015]
[0016] (In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0017]
[0018] (In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. m is 0, 1 or 2.
[0019]
[0020] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0021] [2] The laminate according to [1] above, wherein the first inorganic film has a thickness of 1 to 1,000 nm, and the second inorganic film has a thickness of 1 to 1,000 nm.
[0022] [3] The laminate according to [1] or [2], wherein at least one of the first inorganic film and the second inorganic film contains silicon.
[0023] [4] The stacked body according to any one of [1] to [3] above, wherein the first inorganic film and the second inorganic film include at least one selected from silicon oxide, silicon nitride, and amorphous silicon.
[0024] [5] A method for manufacturing a laminate, comprising: a step of coating a varnish comprising a polyimide resin and an organic solvent on a glass support substrate and a first inorganic film laminated on the aforementioned support substrate, and heating the varnish at a temperature above 400° C.; and a step of laminating a second inorganic film, wherein the aforementioned polyimide resin has a structural unit of the following general formula (1) or a structural unit of the following general formula (2).
[0025]
[0026] (In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0027]
[0028] (In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. m is 0, 1 or 2.
[0029]
[0030] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0031] [6] A method for manufacturing a laminate, comprising: a step of coating a varnish containing a polyimide resin precursor and an organic solvent on a glass support substrate and a first inorganic film laminated on the aforementioned support substrate, and heating the varnish at a temperature above 400°C; and a step of laminating a second inorganic film, wherein the aforementioned polyimide resin precursor has a structural unit of the following general formula (4) or a structural unit of the following general formula (5).
[0032]
[0033] (In formula (4), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. 3 , R 4 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0034]
[0035] (In formula (5), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 5 , R 6 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. m is 0, 1 or 2.
[0036]
[0037] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0038] [7] A method for producing a laminate for a TFT substrate, wherein a TFT functional layer is stacked on the second inorganic film in the laminate according to any one of [1] to [4], and the first inorganic film is peeled off from the interface with the polyimide resin.
[0039] [8] A laminate for a TFT substrate, obtained by the production method described in [7].
[0040] [9] An electronic device comprising the laminate for a TFT substrate according to [8] above.
[0041] Effects of the Invention
[0042] According to the present invention, it is possible to provide a laminate and a production method for a TFT substrate which are excellent in heat resistance, have a low yellowness, and further have a small change in yellowness after heat treatment. DETAILED DESCRIPTION
[0043] [Laminated body]
[0044] The laminate of the present invention is a laminate for manufacturing a TFT substrate, which comprises: a glass supporting substrate, a first inorganic film laminated on the aforementioned supporting substrate, a polyimide resin laminated on the aforementioned first inorganic film, and a second inorganic film laminated on the aforementioned polyimide resin, wherein the aforementioned polyimide resin has a structural unit of the following general formula (1) or a structural unit of the following general formula (2), and has a glass transition temperature of above 400°C.
[0045]
[0046] (In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0047]
[0048] (In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. m is 0, 1 or 2.
[0049]
[0050] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0051] <Polyimide resin>
[0052] First, the polyimide resin laminated on the first inorganic film will be described.
[0053] The polyimide resin contained in the laminate of the present invention has a structural unit of the following general formula (1) or a structural unit of the following general formula (2), and has a glass transition temperature of 400° C. or higher.
[0054]
[0055] (In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0056]
[0057] (In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. m is 0, 1 or 2.
[0058]
[0059] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0060] Hereinafter, a polyimide resin having a structural unit of the general formula (1) and a glass transition temperature of 400°C or higher is referred to as polyimide resin (1), and a polyimide resin having a structural unit of the general formula (2) and a glass transition temperature of 400°C or higher is referred to as polyimide resin (2).
[0061] As the polyimide resin used for the laminated body of the present invention, the polyimide resin (1) is more preferable.
[0062] The glass transition temperature of the polyimide resin contained in the laminate of the present invention is 400°C or higher. The glass transition temperature of the polyimide resin contained in the laminate of the present invention is preferably 410°C or higher, more preferably 420°C or higher, further preferably 430°C or higher, further preferably 440°C or higher, further preferably 450°C or higher. There is no upper limit, but it is preferably 550°C or lower. By setting the glass transition temperature of the polyimide resin to the above range, the laminate of the present invention becomes excellent in heat resistance and is useful as a laminate for manufacturing a TFT substrate.
[0063] The laminate of the present invention is excellent as a laminate for manufacturing a TFT substrate, and the obtained laminate has excellent heat resistance, low yellowness, and small change in yellowness after heat treatment. The reason why the laminate of the present invention has such excellent properties is not clear, but it is considered as follows.
[0064] As polyimides with low yellowness, polyimides using acid dianhydrides and diamines having substituents such as fluoro groups, trifluoromethyl groups, and methyl groups on aromatic rings are known. When the polyimide having substituents such as fluoro groups, trifluoromethyl groups, and methyl groups is kept at a high temperature of 400°C or above, it is easy to decompose and degrade due to trace outgassing generated from the glass that becomes the supporting substrate, or trace gas generated by the reaction of the polyimide with the glass that becomes the supporting substrate, resulting in deterioration of the yellowness. On the other hand, it is believed that the laminate of the present invention contains a polyimide resin with excellent heat resistance having a glass transition temperature of 400°C or above, and the first inorganic film suppresses the trace outgassing generated from the glass that becomes the supporting substrate when the high temperature is kept above 400°C, and suppresses the reaction of the polyimide with the glass that becomes the supporting substrate, thereby suppressing the decomposition and degradation of the polyimide resin, especially at high temperature, thereby having both heat resistance and low yellowness, and suppressing the change of yellowness even after heat treatment.
[0065] (Polyimide resin (1))
[0066] The polyimide resin (1) has a structural unit represented by the following general formula (1) and has a glass transition temperature of 400° C. or higher.
[0067]
[0068] (In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring structure, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0069] In the above formula (1), X 1 It is a tetravalent group having an alicyclic structure or an aromatic ring. 1 It is preferably a product obtained by removing two dicarboxylic acid anhydride moieties (four carboxyl group moieties) from tetracarboxylic acid dianhydride serving as a raw material of structural unit A1 derived from tetracarboxylic dianhydride described later.
[0070] From the perspective of heat resistance, X 1It preferably contains a tetravalent group having an aromatic ring, more preferably consists of a tetravalent group having an aromatic ring, and further preferably consists of only a tetravalent group having an aromatic ring.
[0071] X in the above formula (1) 1 It is more preferred that the compound contains at least one selected from the group consisting of a quadrivalent group represented by formula (3), a quadrivalent group represented by formula (6), a quadrivalent group represented by formula (7), a quadrivalent group represented by formula (8), a quadrivalent group represented by formula (9), and a quadrivalent group represented by formula (10). It is further preferred that the compound contains at least one selected from the group consisting of a quadrivalent group represented by formula (3), a quadrivalent group represented by formula (6), a quadrivalent group represented by formula (7), a quadrivalent group represented by formula (8), and a quadrivalent group represented by formula (10). It is further preferred that the compound contains at least one selected from the group consisting of a quadrivalent group represented by formula (3), a quadrivalent group represented by formula (6), a quadrivalent group represented by formula (7), a quadrivalent group represented by formula (8), and a quadrivalent group represented by formula (10). The invention further preferably contains at least one of the group consisting of a group, a quadrivalent group represented by formula (7) and a quadrivalent group represented by formula (8), further preferably contains the quadrivalent group represented by formula (7) and contains any of the quadrivalent group represented by formula (6), the quadrivalent group represented by formula (8) or the quadrivalent group represented by formula (10), further preferably contains the quadrivalent group represented by formula (7) and contains any of the quadrivalent group represented by formula (8) or the quadrivalent group represented by formula (10), further preferably contains the quadrivalent group represented by formula (7) and contains any of the quadrivalent group represented by formula (8) or the quadrivalent group represented by formula (10), further preferably contains the quadrivalent group represented by formula (7) and the quadrivalent group represented by formula (8) and the quadrivalent group represented by formula (8).
[0072]
[0073] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0074] By making X 1 The inclusion of the tetravalent group represented by the formula (7) provides a laminate having excellent heat resistance.
[0075] In the above formula (3), each R is independently a methyl group or a trifluoromethyl group, and is preferably a methyl group.
[0076] p is an integer of 1 to 4, and p is preferably 3.
[0077] k is 1 or 2, but preferably k is 2.
[0078] The tetravalent group represented by the above formula (3) is preferably a tetravalent group represented by the formula (31), and is more preferably a tetravalent group represented by the formula (32) from the viewpoint of heat resistance and reduction of yellowness.
[0079]
[0080] (In formula (31), R is independently a methyl group, a fluoro group or a trifluoromethyl group, and p is an integer of 1 to 4.)
[0081] Y 1 It is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group, preferably at least one selected from the group consisting of a single bond, -COO-, -OCO- and a fluorenylene group, and more preferably a single bond. 1 It can be the same or different.
[0082] R 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group, and is preferably a trifluoromethyl group.
[0083] h and i are integers of 0 to 4, and at least one of them is an integer of 1 to 4. At least one of all of h and i is an integer of 1 to 4. That is, when n is 1, at least one of h and i is an integer of 1 to 4. When n is 2, at least one of h and a plurality of i is an integer of 1 to 4. h and i are preferably 0 or 1, and more preferably 1.
[0084] n is 0, 1 or 2, preferably 1.
[0085] The polyimide resin (1) may have a structural unit of the following general formula (11). From the viewpoint of further improving heat resistance, the polyimide resin (1) preferably has a structural unit of the following general formula (11).
[0086]
[0087] (In formula (11), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring structure, Y 3 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. q is 0, 1 or 2.)
[0088] In the above formula (11), X 1 Similar to the above formula (1), it is a tetravalent group having an alicyclic structure or an aromatic ring. 1 It is preferably a product obtained by removing two dicarboxylic acid anhydride moieties (four carboxyl group moieties) from tetracarboxylic acid dianhydride serving as a raw material of structural unit A1 derived from tetracarboxylic dianhydride described later.
[0089] Y 3It is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group, preferably at least one selected from the group consisting of a single bond, -COO-, -OCO- and a fluorenylene group, more preferably -COO- and -OCO- from the viewpoint of heat resistance, and more preferably a fluorenylene group from the viewpoint of yellowing inhibition. 3 It can be the same or different.
[0090] q is 0, 1 or 2, preferably 1.
[0091] When the polyimide resin (1) has a structural unit of the formula (11), the molar ratio of the structural unit of the formula (1) to the structural unit of the formula (11) [(1):(11)] is preferably 20:80 to 90:10, more preferably 20:80 to 80:20, and from the viewpoint of suppressing yellowing, it is further preferably 30:70 to 80:20, further preferably 50:50 to 80:20, further preferably 50:50 to 70:30. From the viewpoint of heat resistance, it is further preferably 20:80 to 70:30, further preferably 20:80 to 50:50, further preferably 30:70 to 50:50.
[0092] (Structural units of polyimide (1))
[0093] The polyimide (1) has a structural unit A1 derived from tetracarboxylic dianhydride and a structural unit B1 derived from a diamine.
[0094] (Structural unit A1)
[0095] The structural unit A1 is a structural unit derived from tetracarboxylic dianhydride. There are no particular restrictions on the structural unit derived from tetracarboxylic dianhydride. It preferably contains at least one selected from the group consisting of structural units derived from aromatic tetracarboxylic dianhydride and structural units derived from alicyclic tetracarboxylic dianhydride, and more preferably contains a structural unit derived from aromatic tetracarboxylic dianhydride.
[0096] Examples of the aromatic tetracarboxylic dianhydride that imparts a structural unit derived from an aromatic tetracarboxylic dianhydride include biphenyltetracarboxylic dianhydride (BPDA), 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (BPAF), pyromellitic dianhydride, 3,3',4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, and a compound represented by the following formula (a4).
[0097] Among them, from the viewpoint of heat resistance, at least one selected from the group consisting of compounds represented by the following formula (a1), compounds represented by the following formula (a2) and compounds represented by the following formula (a4) is preferred, and compounds represented by the following formula (a1) are more preferred.
[0098] That is, the structural unit A1 preferably includes at least one selected from the group consisting of a structural unit (A11) derived from a compound represented by the following formula (a1), a structural unit (A12) derived from a compound represented by the following formula (a2), and a structural unit (A14) derived from a compound represented by the following formula (a4), more preferably includes the structural unit (A11) derived from a compound represented by the following formula (a1), and more preferably includes the structural unit (A11) derived from a compound represented by the following formula (a1) and a structural unit (A12) derived from a compound represented by the following formula (a2).
[0099]
[0100] (In formula (a4), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0101] The compound represented by formula (a1) is biphenyltetracarboxylic dianhydride (BPDA), and specific examples thereof include: 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) represented by the following formula (a1s), 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA) represented by the following formula (a1a), and 2,2',3,3'-biphenyltetracarboxylic dianhydride (i-BPDA) represented by the following formula (a1i). Among them, 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) represented by the following formula (a1s) is preferred.
[0102]
[0103] The compound represented by formula (a2) is 9,9′-bis(3,4-dicarboxyphenyl)fluorene dianhydride (BPAF).
[0104] In the above formula (a4), each R is independently a methyl group or a trifluoromethyl group, and is preferably a methyl group.
[0105] p is an integer of 1 to 4, and preferably p is 3.
[0106] That is, from the viewpoint of heat resistance and reduction of yellowness, the structural unit (A14) derived from the compound represented by formula (a4) preferably includes a structural unit (A141) derived from a compound represented by the following formula (a41), and preferably includes a structural unit (A142) derived from a compound represented by the following formula (a42).
[0107]
[0108] (In formula (a41), each R is independently a methyl group, a fluoro group or a trifluoromethyl group, and p is an integer of 1 to 4.)
[0109] The compound represented by formula (a42) is 2,2',3,3',5,5'-hexamethyl[1,1'-biphenyl]-4,4'-diyl=bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-carboxylate) (TMPBP-TME).
[0110] Examples of the alicyclic tetracarboxylic dianhydride that imparts a structural unit derived from an alicyclic tetracarboxylic dianhydride include 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic dianhydride (CpODA), bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (BODA), decahydro-1,4:5,8-dimethylnaphthalene-2,3,6,7-tetracarboxylic dianhydride, and the like. anhydride (DNDA), dicyclohexyltetracarboxylic dianhydride, 5,5'-1,4-(phenylene)-bis[hexahydro-4,7-methanoisobenzofuran-1,3-dione] (5,5'-(1,4-phenylene)-bis[hexahydro-4,7-methanoisobenzofuran-1,3-dione]), 5,5'-bis-2-norbornene-5,5',6,6'-tetracarboxylic acid-5,5',6,6'-dianhydride, or positional isomers thereof.
[0111] Among them, at least one selected from the group consisting of the compound represented by the following formula (a3), the compound represented by the following formula (a5) and the compound represented by the following formula (a6) is preferred, at least one selected from the group consisting of the compound represented by the following formula (a3) and the compound represented by the following formula (a6) is more preferred, and the compound represented by the following formula (a3) is further preferred.
[0112] That is, the structural unit A1 preferably includes at least one selected from the group consisting of a structural unit (A13) derived from a compound represented by the following formula (a3), a structural unit (A15) derived from a compound represented by the following formula (a5), and a structural unit (A16) derived from a compound represented by the following formula (a6), and more preferably includes at least one selected from the group consisting of a structural unit (A13) derived from a compound represented by the following formula (a3) and a structural unit (A16) derived from a compound represented by the following formula (a6). From the viewpoint of suppressing yellowing, it is further preferred to include a structural unit (A13) derived from a compound represented by the following formula (a3). From the viewpoint of heat resistance, it is preferred to include a structural unit (A16) derived from a compound represented by the following formula (a6).
[0113]
[0114] The structural unit A1 may include structural units other than structural units derived from aromatic tetracarboxylic dianhydrides and structural units derived from alicyclic tetracarboxylic dianhydrides. The tetracarboxylic dianhydrides that provide such structural units are not particularly limited, and aliphatic tetracarboxylic dianhydrides may be cited. As aliphatic tetracarboxylic dianhydrides that provide structural units derived from aliphatic tetracarboxylic dianhydrides, 1,2,3,4-butanetetracarboxylic dianhydride may be cited.
[0115] The structural unit optionally contained in the structural unit A1 may be one kind or two or more kinds.
[0116] In the present specification, aromatic tetracarboxylic dianhydride refers to a tetracarboxylic dianhydride containing one or more aromatic rings, alicyclic tetracarboxylic dianhydride refers to a tetracarboxylic dianhydride containing one or more alicyclic rings and no aromatic ring, and aliphatic tetracarboxylic dianhydride refers to a tetracarboxylic dianhydride containing neither an aromatic ring nor an alicyclic ring.
[0117] (Structural unit B1)
[0118] The structural unit B1 is a structural unit derived from a diamine. There are no particular limitations on the structural unit as long as it is a structural unit derived from a diamine, but it preferably includes a structural unit derived from an aromatic diamine, and more preferably a structural unit derived from an aromatic diamine.
[0119] Examples of the aromatic diamine to which the structural unit derived from the aromatic diamine is added include 2,2'-bis(trifluoromethyl)benzidine (TFMB), 4-aminobenzoic acid-4-aminophenyl ester (4-BAAB), 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ), bis(4-aminophenyl)terephthalate (APTP), 9,9-bis(4-aminophenyl)fluorene (BAFL), 3,5-diaminobenzoic acid (3,5-DABA), 1,4-phenylenediamine, p-phenylenediamine, 1,5-diaminonaphthalene, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-dimethylbiphenyl-4,4 '-diamine, 4,4'-diaminodiphenylmethane, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminobenzanilide, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-inden-5-amine, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, N,N'-bis(4-aminophenyl)terephthalamide, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and 1,4-bis(4-aminophenoxy)benzene, 2,2"-bis(trifluoromethyl)[1,1':4 ',1"-terphenyl]-4,4"-diamine (2,2"-Bis(trifluoromethyl)[1,1':4',1"-terphenyl]-4,4"-diamine, 2,2',5',2"-Tetra(trifluoromethyl)-[1,1':4',1"-terphenyl]-4,4"-diamine, 1,4-Bis(trifluoromethyl)-2,5-diaminobenzene, 2,5-difluorobenzene-1,4-diamine, 2-(trifluoromethyl)-1,4-phenylenediamine, 2-fluorobenzene-1,4-diamine, 4,4'-diamino-2,2'-difluorobiphenyl, 4'-aminobenzoic acid-4-amino-2-fluorophenyl ester, 4'-aminobenzoic acid-4-amino-3-fluorophenyl ester, 4'-aminobenzoic acid-4-amino-3-methylphenyl ester, 4'-aminobenzoic acid-4-amino-3,5-difluorophenyl ester, 4'-aminobenzoic acid-4-amino-3,5-dimethylphenyl ester, 4'-amino-3'-methylbenzoic acid-4-amino-3-methylphenyl ester, 4'-aminobenzoic acid-4-amino-2-methyl ester, etc.
[0120] Among them, from the viewpoint of heat resistance and yellowness, it is preferred to be at least one selected from the group consisting of a compound represented by the following formula (b11), a compound represented by the following formula (b12), a compound represented by the following formula (b13), a compound represented by the following formula (b2), and a compound represented by the following formula (b3). It is more preferred to be at least one selected from the group consisting of a compound represented by the following formula (b11), a compound represented by the following formula (b12), a compound represented by the following formula (b13), and a compound represented by the following formula (b2). It is further preferred to be at least one selected from the group consisting of a compound represented by the following formula (b11), a compound represented by the following formula (b12), and a compound represented by the following formula (b13). It is further preferred to be a compound represented by the following formula (b11). Two or more aromatic diamines may be used in combination. When two or more aromatic diamines are used in combination, it is further preferred to be a compound represented by the following formula (b11) and a compound represented by the following formula (b2) or a compound represented by the following formula (b3). It is further preferred to be a compound represented by the following formula (b11) and a compound represented by the following formula (b2).
[0121] That is, from the viewpoint of heat resistance and yellowness, the structural unit B1 preferably includes at least one selected from the group consisting of a structural unit (B111) derived from a compound represented by the following formula (b11), a structural unit (B112) derived from a compound represented by the following formula (b12), a structural unit (B113) derived from a compound represented by the following formula (b13), a structural unit (B12) derived from a compound represented by the following formula (b2), and a structural unit (B13) derived from a compound represented by the following formula (b3), and more preferably includes a structural unit (B111) derived from a compound represented by the following formula (b11), a structural unit (B112) derived from a compound represented by the following formula (b12), The present invention further preferably comprises at least one of the structural units (B112) derived from the compound represented by the following formula, the structural unit (B113) derived from the compound represented by the following formula (b13), and the structural unit (B12) derived from the compound represented by the following formula (b2). It further preferably comprises at least one of the structural units (B111) derived from the compound represented by the following formula (b11), the structural unit (B112) derived from the compound represented by the following formula (b12), and the structural unit (B113) derived from the compound represented by the following formula (b13). It further preferably comprises the structural unit (B111) derived from the compound represented by the following formula (b11). The structural unit derived from an aromatic diamine contained in the structural unit B1 may include two or more types. When it contains two or more types, it is further preferred to contain a structural unit (B111) derived from a compound represented by the following formula (b11) and a structural unit (B12) derived from a compound represented by the following formula (b2) or a structural unit (B13) derived from a compound represented by the following formula (b3), and it is further preferred to contain a structural unit (B111) derived from a compound represented by the following formula (b11) and a structural unit (B12) derived from a compound represented by the following formula (b2).
[0122]
[0123] The compound represented by formula (b11) is 2,2′-bis(trifluoromethyl)benzidine (TFMB).
[0124] The compound represented by formula (b12) is 2,2"-bis(trifluoromethyl)[1,1':4',1"-terphenyl]-4,4"-diamine.
[0125] The compound represented by formula (b13) is 2,2',5',2"-tetrakis(trifluoromethyl)-[1,1':4',1"-terphenyl]-4,4"-diamine.
[0126] The compound represented by formula (b2) is 4-aminophenyl 4-aminobenzoate (4-BAAB).
[0127] The compound represented by formula (b3) is 9,9-bis(4-aminophenyl)fluorene (BAFL).
[0128] The structural unit B1 may contain structural units other than the structural unit derived from the aromatic diamine. Such structural units are not particularly limited, and examples thereof include structural units derived from alicyclic diamines and structural units derived from aliphatic diamines.
[0129] As an alicyclic diamine which provides the structural unit derived from an alicyclic diamine, 1, 3- bis (aminomethyl) cyclohexane, 1, 4- bis (aminomethyl) cyclohexane, etc. are mentioned.
[0130] Examples of the aliphatic diamine for providing the structural unit derived from the aliphatic diamine include ethylenediamine and hexamethylenediamine.
[0131] The structural unit optionally contained in the structural unit B1 may be one kind or two or more kinds.
[0132] In the present specification, aromatic diamine refers to a diamine containing one or more aromatic rings, alicyclic diamine refers to a diamine containing one or more alicyclic rings and no aromatic ring, and aliphatic diamine refers to a diamine containing neither an aromatic ring nor an alicyclic ring.
[0133] (Polyimide resin (2))
[0134] The polyimide resin (2) has a structural unit represented by the following general formula (2) and has a glass transition temperature of 400° C. or higher.
[0135]
[0136] (In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. m is 0, 1 or 2.
[0137]
[0138] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0139] In the above formula (2), X 2 Contains a tetravalent group represented by the above general formula (3). 2 It is preferably a product obtained by removing two dicarboxylic acid anhydride moieties (four carboxyl group moieties) from tetracarboxylic acid dianhydride serving as a raw material of structural unit A2 derived from tetracarboxylic dianhydride described later.
[0140] In the above formula (3), each R is independently a methyl group or a trifluoromethyl group, and is preferably a methyl group.
[0141] p is an integer of 1 to 4, and p is preferably 3.
[0142] k is 1 or 2, but preferably k is 2.
[0143] The tetravalent group represented by the above formula (3) is preferably a tetravalent group represented by the formula (31), and is more preferably a tetravalent group represented by the formula (32) from the viewpoint of heat resistance and reduction of yellowness.
[0144]
[0145] (In formula (31), R is independently a methyl group, a fluoro group or a trifluoromethyl group, and p is an integer of 1 to 4.)
[0146] Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene, and preferably at least one selected from the group consisting of -COO- and -OCO-. 2 It can be the same or different.
[0147] m is 0, 1 or 2, preferably 1.
[0148] (Structural units of polyimide (2))
[0149] The polyimide (2) has a structural unit A2 derived from tetracarboxylic dianhydride and a structural unit B2 derived from a diamine.
[0150] (Structural unit A2)
[0151] The structural unit A2 is a structural unit derived from tetracarboxylic dianhydride, and contains a structural unit (A21) derived from a compound represented by the following formula (a4).
[0152]
[0153] (In formula (a4), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0154] In the above formula (a4), each R is independently a methyl group or a trifluoromethyl group, and is preferably a methyl group.
[0155] p is an integer of 1 to 4, and p is preferably 3.
[0156] That is, from the viewpoint of heat resistance and reduction of yellowness, the structural unit (A21) derived from the compound represented by formula (a4) preferably includes a structural unit (A211) derived from a compound represented by the following formula (a41), and preferably includes a structural unit (A212) derived from a compound represented by the following formula (a42).
[0157]
[0158] (In formula (a41), R is independently a methyl group, a fluoro group or a trifluoromethyl group, and p is an integer of 1 to 4.)
[0159] The compound represented by formula (a42) is 2,2',3,3',5,5'-hexamethyl[1,1'-biphenyl]-4,4'-diyl=bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-carboxylate) (TMPBP-TME).
[0160] Structural unit A2 may also include structural units other than aromatic tetracarboxylic dianhydride. There is no particular limitation on the tetracarboxylic dianhydride that provides such a structural unit, and examples thereof include: structural units derived from aromatic tetracarboxylic dianhydride other than the structural unit (A21) derived from the compound represented by formula (a4), structural units derived from alicyclic tetracarboxylic dianhydride, and aliphatic tetracarboxylic dianhydride. The structural units derived from aromatic tetracarboxylic dianhydride other than the structural unit (A21) derived from the compound represented by formula (a4), structural units derived from alicyclic tetracarboxylic dianhydride, and aliphatic tetracarboxylic dianhydride are the same as those described in (structural unit A1) in the polyimide resin (1).
[0161] The structural unit optionally contained in the structural unit A2 may be one kind or two or more kinds.
[0162] (Structural unit B2)
[0163] The structural unit B2 is a structural unit derived from a diamine. There are no particular limitations on the structural unit as long as it is a structural unit derived from a diamine, but it preferably includes a structural unit derived from an aromatic diamine, and more preferably a structural unit derived from an aromatic diamine.
[0164] Examples of the aromatic diamine to which the structural unit derived from the aromatic diamine is added include 2,2'-bis(trifluoromethyl)benzidine (TFMB), 4-aminobenzoic acid-4-aminophenyl ester (4-BAAB), 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ), bis(4-aminophenyl)terephthalate (APTP), 9,9-bis(4-aminophenyl)fluorene (BAFL), 3,5-diaminobenzoic acid (3,5-DABA), 1,4-phenylenediamine, p-phenylenediamine, 1,5-diaminonaphthalene, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-dimethylbiphenyl-4,4 '-diamine, 4,4'-diaminodiphenylmethane, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminobenzanilide, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-inden-5-amine, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, N,N'-bis(4-aminophenyl)terephthalamide, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and 1,4-bis(4-aminophenoxy)benzene, 2,2"-bis(trifluoromethyl)[1,1':4 ',1"-terphenyl]-4,4"-diamine (2,2"-Bis(trifluoromethyl)[1,1':4',1"-terphenyl]-4,4"-diamine, 2,2',5',2"-Tetra(trifluoromethyl)-[1,1':4',1"-terphenyl]-4,4"-diamine, 1,4-Bis(trifluoromethyl)-2,5-diaminobenzene, 2,5-difluorobenzene-1,4-diamine, 2-(trifluoromethyl)-1,4-phenylenediamine, 2-fluorobenzene-1,4-diamine, 4,4'-diamino-2,2'-difluorobiphenyl, 4'-aminobenzoic acid-4-amino-2-fluorophenyl ester, 4'-aminobenzoic acid-4-amino-3-fluorophenyl ester, 4'-aminobenzoic acid-4-amino-3-methylphenyl ester, 4'-aminobenzoic acid-4-amino-3,5-difluorophenyl ester, 4'-aminobenzoic acid-4-amino-3,5-dimethylphenyl ester, 4'-amino-3'-methylbenzoic acid-4-amino-3-methylphenyl ester, 4'-aminobenzoic acid-4-amino-2-methyl ester, etc.
[0165] Among them, from the viewpoint of heat resistance, a compound represented by the following formula (b2) is preferred.
[0166] That is, the structural unit B2 preferably includes a structural unit (B21) derived from a compound represented by the following formula (b2).
[0167]
[0168] The compound represented by formula (b2) is 4-aminophenyl 4-aminobenzoate (4-BAAB).
[0169] The structural unit B2 may contain structural units other than the structural unit derived from the aromatic diamine. There are no particular restrictions on the diamine that provides such a structural unit, and examples thereof include alicyclic diamines and aliphatic diamines.
[0170] As an alicyclic diamine which provides the structural unit derived from an alicyclic diamine, 1, 3- bis (aminomethyl) cyclohexane, 1, 4- bis (aminomethyl) cyclohexane, etc. are mentioned.
[0171] Examples of the aliphatic diamine for providing the structural unit derived from the aliphatic diamine include ethylenediamine and hexamethylenediamine.
[0172] The structural unit optionally contained in the structural unit B2 may be one kind or two or more kinds.
[0173] (Production Method of Polyimide Resin and Polyimide Resin Precursor)
[0174] The polyimide resin may be produced by any method, but is preferably produced by the following method.
[0175] The polyimide resin can be obtained directly by polymerizing a diamine (hereinafter also referred to as a diamine component) and a tetracarboxylic dianhydride (hereinafter also referred to as a tetracarboxylic dianhydride) or by polymerizing a diamine and a tetracarboxylic dianhydride to obtain a precursor of the polyimide resin, i.e., a polyamic acid or an imide-amic acid copolymer, and then imidizing the polyimide resin when manufacturing a laminate.
[0176] Here, the production method of the imide-amic acid copolymer which is a polyimide resin precursor, the polyamic acid, and the production method of the polyimide resin which directly obtains the polyimide resin are demonstrated.
[0177] (Method for producing imide-amic acid copolymer as a polyimide resin precursor)
[0178] A preferred method for producing a polymer containing both an imide unit and an amic acid unit (hereinafter also referred to as an imide-amic acid copolymer) includes the following step 1 and the following step 2.
[0179] Step 1: A step of reacting tetracarboxylic dianhydride and diamine in the presence of a solvent to obtain an imide oligomer
[0180] Step 2: A step of mixing the imide oligomer obtained in step 1 and at least one of tetracarboxylic dianhydride and diamine, and polymerizing the mixture.
[0181] [Process 1]
[0182] Step 1 is a step of reacting tetracarboxylic dianhydride and diamine constituting the imide portion in the presence of a solvent to obtain an imide oligomer.
[0183] In step 1, the amount of diamine is preferably 1.01 to 2 mol, more preferably 1.05 to 1.9 mol, and even more preferably 1.1 to 1.7 mol, based on tetracarboxylic dianhydride.
[0184] The method for reacting tetracarboxylic dianhydride and diamine to obtain an imide oligomer in step 1 is not particularly limited, and a known method can be used.
[0185] Specific reaction methods include: (1) a method in which tetracarboxylic dianhydride, a diamine and a solvent are placed in a reactor, stirred at 10 to 110° C. for 0.5 to 30 hours, and then the temperature is raised to carry out an imidization reaction; (2) a method in which a diamine and a solvent are placed in a reactor and dissolved, and then tetracarboxylic dianhydride is placed in the reactor, stirred at 10 to 110° C. for 0.5 to 30 hours as required, and then the temperature is raised to carry out an imidization reaction; (3) a method in which tetracarboxylic dianhydride, a diamine and a solvent are placed in a reactor, and the temperature is immediately raised to carry out an imidization reaction, etc.
[0186] In the imidization reaction, it is preferred to carry out the reaction while removing water generated during the production using a Dean-Stark apparatus, etc. By performing such an operation, the degree of polymerization and the imidization ratio can be further increased.
[0187] In the above-mentioned imidization reaction, a known imidization catalyst can be used. Examples of the imidization catalyst include a base catalyst and an acid catalyst.
[0188] Examples of the base catalyst include organic base catalysts such as pyridine, quinoline, isoquinoline, α-methylpyridine, β-methylpyridine, 2,4-lutidine, 2,6-lutidine, trimethylamine, triethylamine, tripropylamine, tributylamine, triethylenediamine, imidazole, N,N-dimethylaniline, and N,N-diethylaniline; and inorganic base catalysts such as potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogen carbonate, and sodium hydrogen carbonate.
[0189] Examples of the acid catalyst include crotonic acid, acrylic acid, trans-3-hexenoic acid, cinnamic acid, benzoic acid, methylbenzoic acid, hydroxybenzoic acid, terephthalic acid, benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid. The imidization catalysts described above may be used alone or in combination of two or more.
[0190] Among the above, from the viewpoint of operability, a base catalyst is preferred, an organic base catalyst is more preferred, at least one selected from triethylamine and triethylenediamine is further preferred, and triethylamine is further preferred.
[0191] From the viewpoint of reaction rate and suppression of gelation, the temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C. The reaction time is preferably 0.5 to 10 hours after the distillation of generated water starts.
[0192] The solution containing the imide oligomer dissolved in the solvent can be obtained by the above method. The solution containing the imide oligomer obtained in step 1 may contain at least a part of the components used as tetracarboxylic dianhydride and diamine in step 1 as unreacted monomers within the range not impairing the effects of the present invention.
[0193] [Process 2]
[0194] Step 2 is a step of mixing the imide oligomer obtained in step 1 and at least one of tetracarboxylic dianhydride and diamine, and polymerizing them.
[0195] It is preferable to set the diamine component in the whole process 1 and the process 2 to 0.9-1.1 mol with respect to the tetracarboxylic acid component.
[0196] In step 2, the method for polymerizing the imide oligomer, tetracarboxylic dianhydride and diamine obtained in step 1 is not particularly limited, and a known method can be used.
[0197] Specific reaction methods include: (1) a method in which an imide oligomer and at least one of tetracarboxylic dianhydride and diamine are introduced into a reactor and stirred at a temperature in the range of 0 to 120° C., preferably in the range of 5 to 80° C., for 1 to 72 hours; (2) a method in which an imide oligomer and a solvent are introduced into a reactor and dissolved, and then at least one of tetracarboxylic dianhydride and diamine is introduced into the reactor and stirred at a temperature in the range of 0 to 120° C., preferably in the range of 5 to 80° C., for 1 to 72 hours.
[0198] When the reaction is carried out at 80° C. or lower, the molecular weight of the copolymer obtained in step 2 does not vary depending on the temperature history during polymerization, and the progress of thermal imidization can be suppressed, so that the copolymer can be produced stably.
[0199] The concentration of the copolymer in the obtained solution is usually in the range of 1 to 50% by mass, preferably 3 to 35% by mass, and more preferably 5 to 30% by mass.
[0200] (Method for producing polyamic acid as a polyimide resin precursor)
[0201] When the polyimide resin precursor is a polyamic acid, a preferred method for producing the polyimide resin precursor is a method of obtaining the polyamic acid by reacting tetracarboxylic dianhydride and diamine in the presence of a solvent.
[0202] The method of polymerizing tetracarboxylic dianhydride and diamine is not particularly limited, and a known method can be used.
[0203] Specific examples of the reaction method include a method in which a solution containing a diamine and a solvent and tetracarboxylic dianhydride are placed in a reactor and stirred at 0 to 120° C., preferably 5 to 80° C., for 1 to 72 hours.
[0204] It is preferable to set the diamine component to 0.9-1.1 mol with respect to the tetracarboxylic acid component.
[0205] When the reaction is carried out at 80° C. or lower, the molecular weight of the polyamic acid does not fluctuate depending on the temperature history during polymerization, and the progress of thermal imidization is suppressed, so the polyamic acid can be stably produced.
[0206] The concentration of the polyamic acid in the obtained solution is usually in the range of 1 to 50% by mass, preferably 3 to 35% by mass, and more preferably 5 to 30% by mass.
[0207] (Method for producing polyimide resin)
[0208] A preferred production method in the case of directly obtaining a polyimide resin is a method of obtaining a polyimide resin by reacting tetracarboxylic dianhydride and diamine in the presence of a solvent.
[0209] The method of polymerizing tetracarboxylic dianhydride and diamine is not particularly limited, and a known method can be used.
[0210] Specific reaction methods include: (1) a method in which a solution containing a diamine and a solvent and tetracarboxylic dianhydride are introduced into a reactor, stirred at 10 to 110° C. for 0.5 to 30 hours as required, and then the temperature is raised to carry out an imidization reaction; (2) a method in which a solution containing a diamine and a solvent and tetracarboxylic dianhydride are introduced into a reactor, and the temperature is immediately raised to carry out an imidization reaction.
[0211] In the imidization reaction, it is preferred to use a Dean-Stark apparatus or the like to carry out the reaction while removing water generated during the production. By performing such an operation, the degree of polymerization and the imidization ratio can be further increased.
[0212] In the above-mentioned imidization reaction, a known imidization catalyst can be used. Examples of the imidization catalyst include a base catalyst and an acid catalyst.
[0213] Examples of the base catalyst include organic base catalysts such as pyridine, quinoline, isoquinoline, α-methylpyridine, β-methylpyridine, 2,4-lutidine, 2,6-lutidine, trimethylamine, triethylamine, tripropylamine, tributylamine, triethylenediamine, imidazole, N,N-dimethylaniline, and N,N-diethylaniline; and inorganic base catalysts such as potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogen carbonate, and sodium hydrogen carbonate.
[0214] Examples of the acid catalyst include crotonic acid, acrylic acid, trans-3-hexenoic acid, cinnamic acid, benzoic acid, methylbenzoic acid, hydroxybenzoic acid, terephthalic acid, benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid. The imidization catalysts described above may be used alone or in combination of two or more.
[0215] Among the above, from the viewpoint of operability, a base catalyst is preferred, an organic base catalyst is more preferred, at least one selected from triethylamine and triethylenediamine is further preferred, and triethylamine is further preferred.
[0216] From the viewpoint of reaction rate and suppression of gelation, the temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C. The reaction time is preferably 0.5 to 10 hours after the distillation of generated water starts.
[0217] The concentration of the polyimide in the obtained solution is usually in the range of 1 to 50% by mass, preferably 3 to 35% by mass, and more preferably 5 to 30% by mass.
[0218] Next, the raw materials and the like used in the production methods of the imide-amic acid copolymer, the polyamic acid, and the polyimide resin will be described.
[0219] [Tetracarboxylic dianhydride]
[0220] The tetracarboxylic dianhydride used as a raw material in the above production method is preferably the tetracarboxylic dianhydride described in the structural unit A1 of the above polyimide resin (1) and the tetracarboxylic dianhydride described in the structural unit A2 of the above polyimide resin (2).
[0221] As tetracarboxylic dianhydride, acid dianhydride can be cited, but it is not limited thereto. As long as it is within the scope of providing the above-mentioned structural unit A1 or structural unit A2, its derivative can also be cited. As the derivative, tetracarboxylic acid (free acid) and alkyl esters of the tetracarboxylic acid can be cited. Among them, acid dianhydride is preferred.
[0222] 〔Diamine〕
[0223] The diamine used as a raw material in the above production method is preferably the diamine described in the structural unit B1 of the above polyimide resin (1) and the diamine described in the structural unit B2 of the above polyimide resin (2).
[0224] As the diamine, diamine can be cited, but it is not limited thereto, and its derivatives may be used as long as it is within the scope of providing the structural unit B in the above-mentioned polymer. As the derivative, diisocyanate corresponding to the diamine can be cited. Among them, diamine is preferred.
[0225] 〔Capping agent〕
[0226] In addition, in the production of the polymer, in addition to the tetracarboxylic acid component and the diamine component, a terminal blocking agent may be used. The terminal blocking agent is preferably used in step 2 in the production of the imide-amic acid copolymer.
[0227] As the end-capping agent, monoamines or dicarboxylic acids are preferred. The amount of the end-capping agent introduced is preferably 0.0001 to 0.1 moles, particularly preferably 0.001 to 0.06 moles, relative to 1 mole of the tetracarboxylic acid component. As monoamine end-capping agents, for example, methylamine, ethylamine, propylamine, butylamine, benzylamine, 4-methylbenzylamine, 4-ethylbenzylamine, 4-dodecylbenzylamine, 3-methylbenzylamine, 3-ethylbenzylamine, aniline, 3-methylaniline, 4-methylaniline, etc. are recommended. Among them, benzylamine and aniline can be suitably used. As dicarboxylic acid end-capping agents, dicarboxylic acids are preferred, and a part of them can also be closed-looped. For example, phthalic acid, phthalic anhydride, 4-chlorophthalic acid, tetrafluorophthalic acid, 2,3-benzophenone dicarboxylic acid, 3,4-benzophenone dicarboxylic acid, cyclopentane-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, etc. are recommended. Among them, phthalic acid and phthalic anhydride can be used preferably.
[0228] 〔Solvent〕
[0229] The solvent used in the method for producing the polymer may be any solvent that can dissolve the produced polymer, and examples thereof include aprotic solvents, phenolic solvents, etheric solvents, and carbonate-based solvents.
[0230] Specific examples of the aprotic solvent include cyclic amides, chain amides, that is, amide-based solvents, phosphorus-containing amide-based solvents, sulfur-containing solvents, ketone-based solvents, and ester-based solvents including cyclic esters.
[0231] Among them, the solvent preferably contains at least one selected from the group consisting of cyclic amides, chain amides, and cyclic esters, and more preferably contains cyclic amides.
[0232] Examples of the cyclic amide include N-methylpyrrolidone, N-methylcaprolactam, and 1,3-dimethylimidazolidinone, and N-methylpyrrolidone is preferred.
[0233] Examples of the chain amide include N,N-dimethylformamide, N,N-dimethylacetamide, and tetramethylurea.
[0234] Examples of the cyclic ester include γ-butyrolactone and γ-valerolactone.
[0235] Examples of other ester solvents include (2-methoxy-1-methylethyl) acetate and the like.
[0236] Examples of the phosphorus-containing amide solvent include hexamethylphosphoramide and hexamethylphosphorotriamide.
[0237] Examples of the sulfur-containing solvent include dimethyl sulfone, dimethyl sulfoxide, and sulfolane.
[0238] Examples of the ketone solvent include acetone, methyl ethyl ketone, cyclohexanone, and methylcyclohexanone.
[0239] Specific examples of the phenolic solvent include phenol, o-cresol, m-cresol, p-cresol, 2,3-dimethylphenol, 2,4-dimethylphenol, 2,5-dimethylphenol, 2,6-dimethylphenol, 3,4-dimethylphenol, and 3,5-dimethylphenol.
[0240] Specific examples of the ether solvent include 1,2-dimethoxyethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, bis[2-(2-methoxyethoxy)ethyl]ether, tetrahydrofuran, and 1,4-dioxane.
[0241] Specific examples of the carbonate-based solvent include diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate.
[0242] Among the above solvents, at least one selected from the group consisting of cyclic amides, chain amides and cyclic esters is preferred, cyclic amides are more preferred, and N-methylpyrrolidone is further preferred. The above solvents may be used alone or in combination of two or more.
[0243] (Polyimide resin precursor)
[0244] The precursor of the polyimide resin used as a raw material of the polyimide resin is preferably as follows: That is, the polyimide resin precursor preferably has a structural unit of the following general formula (4) or a structural unit of the following general formula (5).
[0245]
[0246] (In formula (4), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. 3 , R 4 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0247]
[0248] (In formula (5), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 5 , R 6 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. m is 0, 1 or 2.
[0249]
[0250] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0251] In the above formula (4), X 1 It is a tetravalent group having an alicyclic structure or an aromatic ring. 1 It is preferably a product obtained by removing two dicarboxylic acid anhydride moieties (four carboxyl group moieties) from tetracarboxylic acid dianhydride serving as a raw material of structural unit A1 derived from tetracarboxylic dianhydride described later.
[0252] From the perspective of heat resistance, X 1 It preferably contains a tetravalent group having an aromatic ring, more preferably consists of a tetravalent group having an aromatic ring, and further preferably consists of only a tetravalent group having an aromatic ring.
[0253] X in the above formula (4) 1It is more preferred that the compound contains at least one selected from the group consisting of a quadrivalent group represented by formula (3), a quadrivalent group represented by formula (6), a quadrivalent group represented by formula (7), a quadrivalent group represented by formula (8), a quadrivalent group represented by formula (9), and a quadrivalent group represented by formula (10). It is further preferred that the compound contains at least one selected from the group consisting of a quadrivalent group represented by formula (3), a quadrivalent group represented by formula (6), a quadrivalent group represented by formula (7), a quadrivalent group represented by formula (8), and a quadrivalent group represented by formula (10). It is further preferred that the compound contains at least one selected from the group consisting of a quadrivalent group represented by formula (3), a quadrivalent group represented by formula (6), a quadrivalent group represented by formula (7), a quadrivalent group represented by formula (8), and a quadrivalent group represented by formula (10). The invention further preferably contains at least one of the group consisting of a group, a quadrivalent group represented by formula (7) and a quadrivalent group represented by formula (8), further preferably contains the quadrivalent group represented by formula (7) and contains any of the quadrivalent group represented by formula (6), the quadrivalent group represented by formula (8) or the quadrivalent group represented by formula (10), further preferably contains the quadrivalent group represented by formula (7) and contains any of the quadrivalent group represented by formula (8) or the quadrivalent group represented by formula (10), further preferably contains the quadrivalent group represented by formula (7) and contains any of the quadrivalent group represented by formula (8) or the quadrivalent group represented by formula (10), further preferably contains the quadrivalent group represented by formula (7) and the quadrivalent group represented by formula (8) and the quadrivalent group represented by formula (8).
[0254]
[0255] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0256] By making X 1 The inclusion of the tetravalent group represented by the formula (7) provides a laminate having excellent heat resistance.
[0257] In the above formula (3), each R is independently a methyl group or a trifluoromethyl group, and is preferably a methyl group.
[0258] p is an integer of 1 to 4, and p is preferably 3.
[0259] k is 1 or 2, but preferably k is 2.
[0260] The tetravalent group represented by the above formula (3) is preferably a tetravalent group represented by the formula (31), and is more preferably a tetravalent group represented by the formula (32) from the viewpoint of heat resistance and reduction of yellowness.
[0261]
[0262] (In formula (31), R is independently a methyl group, a fluoro group or a trifluoromethyl group, and p is an integer of 1 to 4.)
[0263] Y 1It is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group, preferably at least one selected from the group consisting of a single bond, -COO-, -OCO- and a fluorenylene group, and more preferably a single bond. 1 It can be the same or different.
[0264] R 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group, and is preferably a trifluoromethyl group.
[0265] R 3 , R 4 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms.
[0266] h and i are integers of 0 to 4, and at least one of them is an integer of 1 to 4. At least one of all of h and i is an integer of 1 to 4. That is, when n is 1, at least one of h and i is an integer of 1 to 4. When n is 2, at least one of h and a plurality of i is an integer of 1 to 4. h and i are preferably 0 or 1, and more preferably 1.
[0267] n is 0, 1 or 2, preferably 1.
[0268] In the above formula (5), X 2 Contains a tetravalent group represented by the above general formula (3). 2 It is preferably a product obtained by removing two dicarboxylic acid anhydride portions (four carboxyl group portions) from the above-mentioned tetracarboxylic acid dianhydride serving as a raw material of the structural unit A2 derived from tetracarboxylic dianhydride.
[0269] R 5 , R 6 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms.
[0270] In the above formula (3), each R is independently a methyl group or a trifluoromethyl group, and is preferably a methyl group.
[0271] p is an integer of 1 to 4, and p is preferably 3.
[0272] k is 1 or 2, but preferably k is 2.
[0273] The tetravalent group represented by the above formula (3) is preferably a tetravalent group represented by the formula (31), and is more preferably a tetravalent group represented by the formula (32) from the viewpoint of heat resistance and reduction of yellowness.
[0274]
[0275] (In formula (31), R is independently a methyl group, a fluoro group or a trifluoromethyl group, and p is an integer of 1 to 4.)
[0276] Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene, and preferably at least one selected from the group consisting of -COO- and -OCO-. 2 It can be the same or different.
[0277] m is 0, 1 or 2, preferably 1.
[0278] The polyimide resin precursor having the structural unit of formula (4) preferably has the structural units of the polyimide (1), namely, the structural unit A1 derived from tetracarboxylic dianhydride and the structural unit B1 derived from diamine. More preferred structural units are also as described above.
[0279] The polyimide resin precursor having the structural unit of formula (5) preferably has the structural units of the polyimide (2), namely, the structural unit A2 derived from tetracarboxylic dianhydride and the structural unit B2 derived from diamine. More preferred structural units are also as described above.
[0280] As described above, the polyimide resin precursor may be an imide-amic acid copolymer. In the case of an imide-amic acid copolymer, the polyimide portion preferably has the same structural units as the aforementioned polyimide resin (1) or the aforementioned polyimide resin (2), and preferably has the same structural units as the aforementioned polyimide resin (1).
[0281] As the polyimide resin precursor, a preferred imide-amic acid copolymer has a structural unit of the above-mentioned general formula (1) similarly to the polyimide resin (1).
[0282] The polyamic acid portion may have a structural unit of the following general formula (12). From the viewpoint of further improving heat resistance, the imide-amic acid copolymer preferably has a structural unit of the following general formula (12).
[0283]
[0284] (In formula (12), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring structure, R 7 , R 8 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. 3 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. q is 0, 1 or 2.)
[0285] In the above formula (12), X 1 Similar to the above formula (1), it is a tetravalent group having an alicyclic structure or an aromatic ring. 1 It is preferably a product obtained by removing two dicarboxylic acid anhydride portions (four carboxyl group portions) from tetracarboxylic acid dianhydride serving as a raw material of the above-mentioned tetracarboxylic acid dianhydride-derived structural unit A1.
[0286] R 7 , R 8 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms.
[0287] Y 3 Each independently represents at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group, preferably at least one selected from the group consisting of a single bond, -COO-, -OCO- and a fluorenylene group, more preferably -COO- and -OCO- from the viewpoint of heat resistance, and more preferably a fluorenylene group from the viewpoint of yellowing inhibition. 3 It can be the same or different.
[0288] q is 0, 1 or 2, preferably 1.
[0289] When the imide-amic acid copolymer has structural units of formula (1) and formula (12), the molar ratio of the structural unit of formula (1) to the structural unit of formula (12) [(1):(12)] is preferably 20:80 to 90:10, more preferably 20:80 to 80:20, and from the viewpoint of suppressing yellowing, it is further preferably 30:70 to 80:20, further preferably 50:50 to 80:20, further preferably 50:50 to 70:30. From the viewpoint of heat resistance, it is further preferably 20:80 to 70:30, further preferably 20:80 to 50:50, further preferably 30:70 to 50:50.
[0290] <Varnish>
[0291] The laminate of the present invention is preferably obtained by a production method comprising the steps of applying a varnish containing a polyimide resin precursor and an organic solvent onto a glass support substrate and a first inorganic film laminated on the support substrate, and heating at 400° C. or higher. Next, the varnish used in the production of the laminate is described.
[0292] The varnish contains the polyimide resin and an organic solvent, or contains a polyimide resin precursor and an organic solvent.
[0293] The solvent is not particularly limited as long as it dissolves the polyimide resin or the polyimide resin precursor, and it is preferred to use the above-mentioned compounds used as solvents in the manufacture of the polyimide resin or the polyimide resin precursor alone or in combination. Among the above-mentioned solvents, it is preferred to include at least one selected from the group consisting of cyclic amides, chain amides, and cyclic esters, more preferably to include cyclic amides, and further preferably to include N-methylpyrrolidone.
[0294] The varnish may be the polyimide resin solution or the polyimide resin precursor solution obtained by the above-mentioned method for producing the polyimide resin or the polyimide resin precursor, or may be a solution obtained by further adding a solvent, or may be a solution obtained by reducing the solvent by concentration or the like.
[0295] In the case of a varnish containing a polyimide resin precursor, from the viewpoint of making the imidization of the amic acid part more efficiently proceed, the varnish may further contain an imidization catalyst and a dehydration catalyst. As an imidization catalyst, an imidization catalyst having a boiling point of 40°C or more and 180°C or less may be used, and an amine compound having a boiling point of 180°C or less may be listed as a preferred imidization catalyst. If it is an imidization catalyst having a boiling point of 180°C or less, there is no concern that the polyimide film obtained during drying at high temperature after the laminate is formed is colored and the appearance is damaged. In addition, if it is an imidization catalyst having a boiling point of 40°C or more, the possibility of volatilization before the imidization is fully carried out can be avoided.
[0296] Examples of the amine compound preferably used as the imidization catalyst include pyridine and picoline. The above imidization catalysts may be used alone or in combination of two or more.
[0297] Examples of the dehydration catalyst include acid anhydrides such as acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, and trifluoroacetic anhydride; and carbodiimide compounds such as dicyclohexylcarbodiimide. These can be used alone or in combination of two or more.
[0298] The polyimide resin or polyimide resin precursor contained in the varnish has solvent solubility, so a high-concentration varnish can be made. The varnish preferably contains 3 to 40% by mass of the polyimide resin or the polyimide resin precursor, more preferably 5 to 40% by mass, and further preferably 10 to 30% by mass. The viscosity of the varnish is preferably 1 to 200 Pa·s, more preferably 2 to 20 Pa·s. The viscosity of the varnish is a value measured at 25°C using an E-type viscometer.
[0299] In addition, within the range that does not impair the required properties of the polyimide film, the varnish may also contain various additives such as inorganic fillers, adhesion promoters, release agents, flame retardants, ultraviolet stabilizers, surfactants, leveling agents, defoaming agents, fluorescent brighteners, crosslinking agents, polymerization initiators, and photosensitizers.
[0300] <Supporting base material>
[0301] The supporting substrate used in the laminate of the present invention is made of glass.
[0302] The type of glass is not particularly limited, and alkali-free glass (borosilicate glass), alkali glass, soda glass, non-fluorescent glass, phosphate-based glass, boric acid-based glass, quartz, and the like can be used.
[0303] In order to improve the adhesion with the inorganic film, the flatness of the upper surface of the glass substrate is preferably high. Specifically, the surface roughness Rmax is preferably 10 μm or less, and Rmax is more preferably 1 μm or less.
[0304] <First Inorganic Film and Second Inorganic Film>
[0305] In the laminate of the present invention, a first inorganic film is laminated on a glass support substrate, and a polyimide resin is laminated on the first inorganic film, and a second inorganic film is laminated on the polyimide resin. In addition, a TFT functional layer can also be laminated on the aforementioned second inorganic film in the laminate thus obtained, and the aforementioned first inorganic film is peeled off from the interface with the polyimide resin to manufacture a laminate (second laminate) for a TFT substrate laminated with a polyimide resin, a second inorganic film, and a TFT functional layer. The TFT substrate laminate is used as a TFT substrate and is included in an electronic device. That is, the laminate of the present invention (the aforementioned first laminate) is a raw material laminate that can be used as a TFT substrate.
[0306] Preferably, at least one of the aforementioned first inorganic film and the aforementioned second inorganic film contains silicon, more preferably at least one of the aforementioned first inorganic film and the aforementioned second inorganic film contains at least one selected from silicon oxide, silicon nitride, and amorphous silicon, further preferably at least one of the aforementioned first inorganic film and the aforementioned second inorganic film is formed of at least one selected from silicon oxide, silicon nitride, and amorphous silicon, and even more preferably at least one of the aforementioned first inorganic film and the aforementioned second inorganic film is formed of at least one selected from silicon oxide and amorphous silicon.
[0307] Among them, it is preferred that both the aforementioned first inorganic film and the aforementioned second inorganic film contain silicon, it is more preferred that the aforementioned first inorganic film and the aforementioned second inorganic film contain at least one selected from silicon oxide, silicon nitride, and amorphous silicon, it is further preferred that the aforementioned first inorganic film and the aforementioned second inorganic film are formed of at least one selected from silicon oxide, silicon nitride, and amorphous silicon, it is even more preferred that the aforementioned first inorganic film and the aforementioned second inorganic film are formed of at least one selected from silicon oxide and amorphous silicon.
[0308] The first inorganic film and the second inorganic film are insulating films. That is, the second inorganic film serves as an insulating film between the polyimide film and the TFT functional layer in the laminate for a TFT substrate described later, functions as a barrier film, and also functions as a buffer film.
[0309] The thickness of the first inorganic film is preferably 1 to 1,000 nm, more preferably 1 to 400 nm, further preferably 10 to 300 nm, and further preferably 20 to 200 nm.
[0310] The thickness of the second inorganic film is preferably 1 to 1,000 nm, more preferably 1 to 400 nm, further preferably 10 to 300 nm, and further preferably 20 to 200 nm.
[0311] [Method for producing laminate, laminate for TFT substrate, and electronic device]
[0312] The laminate of the present invention can be obtained by any production method as long as it has the above-mentioned structure, but is preferably produced by the following method.
[0313] Specifically, there can be mentioned a method of producing using a varnish containing the polyimide resin described above and a method of producing using the polyimide resin precursor described above.
[0314] The method for manufacturing a laminate using a varnish containing a polyimide resin comprises the following steps: a step of coating a varnish containing a polyimide resin and an organic solvent on a glass supporting substrate and a first inorganic film stacked on the aforementioned supporting substrate, and heating the coating to above 400°C, and a step of stacking a second inorganic film; the aforementioned polyimide resin has a structural unit of the following general formula (1) or a structural unit of the following general formula (2).
[0315]
[0316] (In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0317]
[0318] (In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene. m is 0, 1 or 2.
[0319]
[0320] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0321] In addition, a method for manufacturing a laminate using a varnish containing a polyimide resin precursor comprises the following steps: a step of coating a varnish containing a polyimide resin precursor and an organic solvent on a glass supporting substrate and a first inorganic film stacked on the aforementioned supporting substrate, and heating the coating at a temperature above 400° C., and a step of stacking a second inorganic film; the aforementioned polyimide resin precursor has a structural unit of the following general formula (4) or a structural unit of the following general formula (5).
[0322]
[0323] (In formula (4), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group. 3 , R 4 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4. n is 0, 1 or 2.
[0324]
[0325] (In formula (5), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group. 5 , R 6 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms. m is 0, 1 or 2.
[0326]
[0327] (In formula (3), R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.)
[0328] The above-mentioned production methods all include the steps of applying a varnish to a glass support substrate and a first inorganic film laminated on the support substrate, and heating the varnish at 400° C. or higher.
[0329] The varnish used in the above-mentioned step has been described in the above-mentioned column of [Varnish], and the same applies to the preferred varnish.
[0330] In addition, the polyimide resin and the polyimide resin precursor are also described in the above-mentioned columns of [polyimide resin] and [polyimide resin precursor], and the preferred polyimide resin and the polyimide resin precursor are also described in the same manner.
[0331] As described above, the method comprises the steps of applying a varnish containing a polyimide resin or a polyimide resin precursor and an organic solvent onto a glass support substrate and a first inorganic film laminated on the support substrate, and heating the varnish at 400° C. or higher.
[0332] Through this process, a preliminary laminate (a laminate that is a raw material of the laminate of the present invention) formed of a glass support substrate, a first inorganic film laminated on the aforementioned support substrate, and a polyimide resin laminated on the aforementioned first inorganic film can be obtained. The laminate of the present invention can be obtained by laminating the second inorganic film on the polyimide resin of the preliminary laminate.
[0333] The heating temperature is preferably 400° C. or higher, more preferably 400 to 500° C. The heating time is usually 1 minute to 6 hours, preferably 5 minutes to 2 hours, more preferably 15 minutes to 1 hour.
[0334] Examples of the heating atmosphere include air, nitrogen, oxygen, hydrogen, and nitrogen / hydrogen mixed gas. In order to suppress coloration of the obtained polyimide resin, nitrogen with an oxygen concentration of 100 ppm or less and nitrogen / hydrogen mixed gas with a hydrogen concentration of 0.5% or less are preferred.
[0335] Next, there is a step of laminating a second inorganic film on the polyimide resin. The second inorganic film may be laminated by any method, but is preferably laminated by sputtering, CVD film formation, or vacuum deposition.
[0336] As the second laminate, a laminate for a TFT substrate (polyimide resin / second inorganic film / TFT functional layer) included in an electronic device is also included in the present invention. The laminate for a TFT substrate is included in the electronic device as a TFT substrate.
[0337] The laminate for a TFT substrate of the present invention can be produced by laminating a TFT functional layer on the second inorganic film in the laminate (first laminate) and peeling the first inorganic film from the interface with the polyimide resin.
[0338] The laminate for TFT substrate is the above-mentioned laminate (first laminate), that is, a laminate comprising a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film, and can be manufactured by laminating a TFT functional layer on the second inorganic film in the laminate, and peeling the first inorganic film from the interface with the polyimide resin. The polyimide resin contained in the laminate has a structural unit of the following general formula (1) or a structural unit of the following general formula (2), and has a glass transition temperature of 400°C or above.
[0339] The method for producing the first stacked body is as described above.
[0340] The TFT functional layer is stacked on the second inorganic film in the first stack (a stack including a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film). Here, the second inorganic film functions as an insulating film between the polyimide film and the TFT functional layer in the stack for the TFT substrate, as a barrier film, and as a buffer film when the TFT functional layer is formed.
[0341] The TFT functional layer is not particularly limited as long as it is a functional layer that can exhibit the functions of an electronic device containing a laminate for a TFT substrate, but it is preferably a layer using at least one semiconductor selected from the group consisting of amorphous silicon, indium gallium zinc oxide (IGZO) and low-temperature polycrystalline silicon (LTPS).
[0342] The manufacturing method of the TFT functional layer is not particularly limited, and an example is shown below. Film-forming metals such as sputtering, evaporation, CVD, and printing are applied, and then exposed after a resist and a photomask are applied, and then etching is performed to form electrodes and metal wiring. On top of it, one or more insulating films, semiconductor films, electrodes, and metal wiring are stacked, and finally a protective layer is formed, thereby obtaining a TFT functional layer.
[0343] Preferred specific examples of metals used for the electrodes and metal wirings include molybdenum, aluminum, etc. Indium tin oxide (ITO) can also be used as a transparent electrode.
[0344] The electronic device of the present invention contains the aforementioned laminate for TFT substrate. That is, it contains the laminate for TFT substrate obtained by the following manufacturing method: laminating a TFT functional layer on the aforementioned second inorganic film in a first laminate (a laminate comprising a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film), and peeling the aforementioned first inorganic film from the interface with the polyimide resin.
[0345] The laminate for TFT substrate obtained by laminating a TFT functional layer on a thin film comprising a polyimide resin and an insulating film can be used for various purposes and can be used as a substrate for electronic devices for display devices such as liquid crystal display panels, OLEDs, quantum dot LED panels, sub-millimeter light emitting diode (mini LED) display panels, and micrometer light emitting diode (micro LED) display panels.
[0346] Example
[0347] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples.
[0348] The polyimide films and laminates obtained in Examples and Comparative Examples were evaluated by the following methods.
[0349] (1) Film thickness of polyimide film after post-baking
[0350] The film thickness of the polyimide film after the post-bake was measured using a digital gauge SA-S110 / 03N manufactured by CITIZEN FINEDEVICE CO., LTD.
[0351] (2) Total light transmittance and yellow index (YI) of polyimide film after post-baking
[0352] The total light transmittance and YI of the post-baked polyimide films of the Examples and Comparative Examples were measured using a color / turbidity simultaneous measuring device "COH7700" manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd., according to JIS K7361-1 for total light transmittance and ASTM E313-05 (illuminant D, 65°) for YI.
[0353] (3) Glass transition temperature (Tg) of polyimide film after post-baking
[0354] The TMA measurement was performed using a thermomechanical analyzer "TMA7100C" manufactured by Hitachi High-Tech Science Corporation, with a sample size of 4 mm×20 mm, in tension mode, under conditions of a load of 50 mN and a heating rate of 10°C / min, with the temperature being raised from 40°C to 500°C, and the inflection point where elongation was observed was extrapolated as the glass transition temperature (Tg).
[0355] (4) Heat resistance of laminate (crack, yellowness index (YI))
[0356] The laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) obtained in the examples and comparative examples was heated for 1 hour (annealing). For the annealing (heating) temperature, the annealing (heating) temperature was 420°C in Examples 1 to 2, 10 and Comparative Examples 1, 7, and 10, 410°C in Examples 4 to 6 and Comparative Examples 3 to 4, and 430°C in Examples 3, 7 to 9, 11 to 12 and Comparative Examples 2, 5 to 6, and 8 to 9. In addition, the higher the annealing (heating) temperature, the more severe the test conditions. Therefore, in the evaluation of the following cracks and yellowness index (YI), if the results are the same, the higher the annealing (heating) temperature, the better the heat resistance.
[0357] (4-1) Crack
[0358] The presence or absence of cracks in the second inorganic film of the laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) after annealing was visually evaluated. The one without cracks had high heat resistance and no adverse conditions during heat treatment, which was good. The results are shown in Table 1 according to the following criteria.
[0359] None: No cracks were observed in the second inorganic film of the laminate after the annealing treatment.
[0360] Yes: Cracks were observed in the second inorganic film of the laminate after the annealing treatment.
[0361] (4-2) Yellowness Index (YI)
[0362] The first inorganic film and the polyimide resin of the laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) after the annealing treatment were peeled off from the interface between the first inorganic film and the polyimide resin to obtain a two-layer laminate (polyimide resin / second inorganic film).
[0363] The YI of the aforementioned 2-layer laminate (polyimide resin / second inorganic film) is measured according to ASTM E313-05 (D light source, 65 °) using the color / turbidity simultaneous measuring device "COH7700" made by NIPPON DENSHOKU INDUSTRIES Co., Ltd. The smaller the value of YI, the less yellowing caused by heating, and the higher the heat resistance of the laminate (support substrate / first inorganic film / polyimide resin / second inorganic film), the better. It should be noted that, as described above, if the value of YI is the same, the annealing (heating) temperature is high and the heat resistance is high. Therefore, if the value of YI is the same, the annealing (heating) temperature is high and the yellowing caused by heating is less, and the heat resistance of the laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) is high, which is good.
[0364] The tetracarboxylic acid component and the diamine component used in the Examples and Comparative Examples and their abbreviations and the like are as follows.
[0365] <Tetracarboxylic acid component>
[0366] CpODA: Norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic dianhydride (compound represented by formula (a3))
[0367] s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride (manufactured by Mitsubishi Chemical Corporation, compound represented by formula (a1s))
[0368] BPAF: 9,9-bis(3,4-dicarboxyphenyl)fluorene anhydride (manufactured by JFE Chemical Co., Ltd.; compound represented by formula (a2))
[0369] TMPBP-TME: 2,2',3,3',5,5'-hexamethyl[1,1'-biphenyl]-4,4'-diyl=bis(1,3-dioxo-1,3-dihydro-2-benzofuran-5-carboxylate) (compound represented by formula (a42))
[0370] DNDA: (4arH,8acH)-decahydro-1t,4t:5c,8c-dimethylnaphthalene-2t,3t,6c,7c-tetracarboxylic dianhydride (manufactured by DAXIN; compound represented by formula (a6))
[0371] <Diamine component>
[0372] TFMB: 2,2'-bis(trifluoromethyl)benzidine (compound represented by formula (b11))
[0373] BAFL: 9,9-bis(4-aminophenyl)fluorene (manufactured by JFE Chemical Co., Ltd.; compound represented by formula (b3))
[0374] 4-BAAB: 4-aminophenyl 4-aminobenzoate (manufactured by Nipponjunryo Chemicals Co., Ltd.; compound represented by formula (b2))
[0375] Diamine (b12): 2,2"-bis(trifluoromethyl)[1,1':4',1"-terphenyl]-4,4"-diamine (manufactured by Luminescence Technology; compound represented by formula (b12))
[0376] Diamine (b13): 2,2',5',2"-tetrakis(trifluoromethyl)-[1,1':4',1"-terphenyl]-4,4"-diamine (synthesized according to the method described in Synthesis Example 1 of JP-A-2022-530104; compound represented by formula (b13))
[0377] The abbreviations and the like of the solvents and catalysts used in Examples and Comparative Examples are as follows.
[0378] NMP: N-methyl-2-pyrrolidone (manufactured by Tokyo Junyaku Industries Co., Ltd.)
[0379] GBL: γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation)
[0380] TEA: triethylamine (manufactured by Kanto Chemical Co., Ltd.)
[0381] Example 1
[0382] (Manufacture of polyimide varnish)
[0383] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, BAFL 13.938 g (0.040 mol), TFMB 19.214 g (0.060 mol), and GBL 126.903 g were charged, and the mixture was stirred at a temperature of 70° C. in a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0384] After adding 23.063 g (0.060 mol) of CpODA, 11.769 g (0.040 mol) of s-BPDA, and 26.967 g of GBL at once to the solution, 0.506 g of TEA and 4.759 g of GBL as imidization catalysts were added, and the temperature in the reaction system was raised to 190° C. over about 20 minutes by heating with a mantle heater. The distilled components were collected, and the rotation speed was adjusted according to the increase in viscosity, while the temperature in the reaction system was kept at 190° C. and refluxed for 5 hours.
[0385] Thereafter, 420.791 g of GBL was added, and the temperature in the reaction system was cooled to 100° C., followed by stirring for about 1 hour to make the mixture uniform, thereby obtaining a polyimide varnish having a solid content concentration of 10% by mass.
[0386] (Manufacturing of Laminated Body)
[0387] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0388] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, and then heated at 400°C in a hot air dryer under a nitrogen atmosphere for 30 minutes to evaporate the solvent, thereby obtaining a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0389] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0390] (Manufacturing of polyimide film (post-baked polyimide film))
[0391] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0392] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0393] Table 1 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0394] Example 2
[0395] In Example 1, except that the first inorganic film was changed to the type described in Table 1, the same procedure as in Example 1 was followed to obtain a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0396] Table 1 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0397] It should be noted that the film thickness was 0.7 mm on a supporting substrate of a glass substrate (AN-100, manufactured by AGC Corporation). An amorphous silicon (a-Si) film is used as the first inorganic film.
[0398] Comparative Example 1
[0399] A laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film) were obtained in the same manner as in Example 1 except that the first inorganic film was not laminated.
[0400] Table 1 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0401] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0402] Example 3
[0403] (Manufacture of polyimide varnish)
[0404] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, BAFL 13.938 g (0.040 mol), TFMB 19.214 g (0.060 mol), and GBL 93.686 g were charged, and the mixture was stirred at a temperature of 70° C. in a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0405] After adding DNDA 18.137g (0.060 mol), s-BPDA 11.769g (0.040 mol) and GBL 19.908g at once to the solution, 5.060g of TEA as an imidization catalyst, 0.056g of triethylenediamine (TEDA) and 3.513g of GBL were added, and the temperature in the reaction system was raised to 190°C over about 20 minutes by heating with a heating mantle. The distilled components were collected, and the rotation speed was adjusted according to the increase in viscosity, while the temperature in the reaction system was maintained at 190°C and refluxed for 5 hours.
[0406] Then, 417.978 g of GBL was added, and the temperature in the reaction system was cooled to 120° C., followed by stirring for about 3 hours to make the mixture uniform, thereby obtaining a polyimide varnish having a solid content concentration of 10% by mass.
[0407] (Manufacturing of Laminated Body)
[0408] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0409] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, and then heated at 430°C in a hot air dryer under a nitrogen atmosphere for 30 minutes to evaporate the solvent, thereby obtaining a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0410] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) composed of a supporting substrate, a first inorganic film, a polyimide resin and a second inorganic film.
[0411] (Manufacturing of polyimide film (post-baked polyimide film))
[0412] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained. Next, the first inorganic film and the polyimide resin were peeled off from the interface to obtain a polyimide film (post-baked polyimide film).
[0413] Table 1 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0414] Comparative Example 2
[0415] In Example 3, except that the first inorganic film was not laminated, the same procedure as in Example 3 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0416] Table 1 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0417] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0418] Example 4
[0419] (Manufacture of polyamic acid varnish)
[0420] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 22.825 g (0.100 mol) of 4-BAAB and 383.95.975 g of NMP were added, and the mixture was stirred at a temperature of 70° C. in a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0421] To this solution, 61.859 g (0.100 mol) of TMPBP-TME and 95.975 g of NMP were added all at once, and the solution was stirred for 5 hours while being maintained at 70° C. using a heating mantle.
[0422] Then, 282.280 g of NMP was added, and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining a polyamic acid varnish having a solid content concentration of 10% by mass.
[0423] (Manufacturing of Laminated Body)
[0424] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0425] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 400°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heated at 400°C in a hot air dryer for 30 minutes to evaporate the solvent, thereby obtaining a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0426] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0427] (Manufacturing of polyimide film (post-baked polyimide film))
[0428] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0429] Then, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0430] Table 2 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0431] Example 5
[0432] In Example 4, except that the first inorganic film was changed to the type described in Table 2, the same procedure as in Example 4 was followed to obtain a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0433] Table 2 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0434] It should be noted that the film thickness was 0.7 mm on a supporting substrate of a glass substrate (AN-100, manufactured by AGC Corporation). An amorphous silicon (a-Si) film is used as the first inorganic film.
[0435] Comparative Example 3
[0436] In Example 4, except that the first inorganic film was not laminated, the same procedure as in Example 4 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0437] Table 2 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0438] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0439] Example 6
[0440] (Manufacture of polyamic acid varnish)
[0441] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 18.260 g (0.080 mol) of diamine (b12), 6.416 g (0.020 mol) of TFMB, and 392.291 g of NMP were added, and the mixture was stirred at a temperature of 70° C. in the system under a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0442] To this solution, 61.859 g (0.100 mol) of TMPBP-TME and 98.073 g of NMP were added all at once, and the solution was stirred for 5 hours while being maintained at 70° C. using a heating mantle.
[0443] Then, 288.449 g of NMP was added, and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining a polyamic acid varnish having a solid content concentration of 10% by mass.
[0444] (Manufacturing of Laminated Body)
[0445] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0446] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 400°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heated at 400°C in a hot air dryer for 30 minutes to evaporate the solvent, thereby obtaining a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0447] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0448] (Manufacturing of polyimide film (post-baked polyimide film))
[0449] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0450] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0451] Table 2 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0452] Comparative Example 4
[0453] In Example 6, except that the first inorganic film was not laminated, the same procedure as in Example 6 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0454] Table 2 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0455] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0456] Example 7
[0457] (Manufacture of imide-amic acid copolymer varnish)
[0458] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 9.607 g (0.030 mol) of TFMB and 46.380 g of NMP were added, and the mixture was stirred at a temperature of 70° C. in a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0459] After adding 9.169 g (0.020 mol) of BPAF and 11.595 g of NMP to the solution at once, 0.152 g of TEA as an imidization catalyst was added, and the temperature in the reaction system was raised to 190° C. over about 20 minutes by heating with a heating jacket. The distilled components were collected, and the rotation speed was adjusted according to the increase in viscosity, while the temperature in the reaction system was maintained at 190° C. and refluxed for 1 hour. Then, 95.849 g of NMP was added, and the temperature in the reaction system was cooled to 50° C. to obtain a solution containing an oligomer having an imide structural unit.
[0460] 23.538 g (0.080 mol) of s-BPDA, 15.978 g (0.070 mol) of 4-BAAB, and 16.858 g of NMP were added to the obtained solution at once, and stirred at 50° C. for 5 hours. Then, NMP was added to make the solid content concentration uniform so as to be 10% by mass, thereby obtaining an imide-amic acid copolymer varnish.
[0461] (Manufacturing of Laminated Body)
[0462] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0463] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 430°C at a heating rate of 5°C / min in a nitrogen atmosphere, heated at 430°C in a hot air dryer for 60 minutes to evaporate the solvent and thermally imidize the substrate to obtain a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by the supporting substrate, the first inorganic film, and the polyimide resin.
[0464] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0465] (Manufacturing of polyimide film (post-baked polyimide film))
[0466] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0467] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0468] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0469] Example 8
[0470] In Example 7, except that the first inorganic film was changed to the type described in Table 3, the same procedure as in Example 7 was followed to obtain a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0471] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0472] It should be noted that the film thickness was 0.7 mm on a supporting substrate of a glass substrate (AN-100, manufactured by AGC Corporation). An amorphous silicon (a-Si) film is used as the first inorganic film.
[0473] Comparative Example 5
[0474] In Example 7, except that the first inorganic film was not laminated, the same procedure as in Example 7 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0475] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0476] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0477] Example 9
[0478] (Manufacture of imide-amic acid copolymer varnish)
[0479] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 12.829 g (0.040 mol) of TFMB and 85.061 g of NMP were charged, and the mixture was stirred at 200 rpm at an internal temperature of 70° C. in a nitrogen atmosphere to obtain a solution.
[0480] After adding 13.753 g (0.030 mol) of BPAF and 21.265 g of NMP to the solution at once, 0.152 g of TEA as an imidization catalyst was added, and the temperature in the reaction system was raised to 190° C. over about 20 minutes by heating with a heating jacket. The distilled components were collected, and the rotation speed was adjusted according to the increase in viscosity, while the temperature in the reaction system was maintained at 190° C. and refluxed for 1 hour. Then, 55.279 g of NMP was added, and the temperature in the reaction system was cooled to 50° C. to obtain a solution containing an oligomer having an imide structural unit.
[0481] 20.618 g (0.070 mol) of s-BPDA, 13.709 g (0.060 mol) of 4-BAAB, and 17.710 g of NMP were added to the obtained solution at once, and stirred at 50° C. for 5 hours. Then, NMP was added to make the solid content concentration uniform so as to be 10% by mass, thereby obtaining an imide-amic acid copolymer varnish.
[0482] (Manufacturing of Laminated Body)
[0483] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0484] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 430°C at a heating rate of 5°C / min in a nitrogen atmosphere, heated at 430°C in a hot air dryer for 60 minutes to evaporate the solvent and thermally imidize the substrate to obtain a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by the supporting substrate, the first inorganic film, and the polyimide resin.
[0485] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0486] (Manufacturing of polyimide film (post-baked polyimide film))
[0487] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0488] Then, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0489] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0490] Comparative Example 6
[0491] In Example 9, except that the first inorganic film was not laminated, the same procedure as in Example 9 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0492] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0493] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0494] Example 10
[0495] (Manufacture of imide-amic acid copolymer varnish)
[0496] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 12.829 g (0.040 mol) of TFMB and 78.938 g of NMP were added, and the mixture was stirred at 200 rpm at an internal temperature of 70° C. in a nitrogen atmosphere to obtain a solution.
[0497] After adding CpODA 11.839g (0.030 mol) and NMP 19.734g at once to the solution, 0.152g of TEA as an imidization catalyst was added, and the temperature in the reaction system was raised to 190°C over about 20 minutes by heating with a heating jacket. The distilled components were collected, and the rotation speed was adjusted according to the increase in viscosity, while the temperature in the reaction system was maintained at 190°C and refluxed for 1 hour. Then, 56.926g of NMP was added, and the temperature in the reaction system was cooled to 50°C to obtain a solution containing an oligomer having an imide structural unit.
[0498] 20.618 g (0.070 mol) of s-BPDA, 13.709 g (0.060 mol) of 4-BAAB, and 17.052 g of NMP were added to the obtained solution at once, and stirred at 50° C. for 5 hours. Then, NMP was added to make the solid content uniform so as to be 10% by mass, thereby obtaining an imide-amic acid copolymer varnish.
[0499] (Manufacturing of Laminated Body)
[0500] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0501] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 400°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heated at 400°C in a hot air dryer for 60 minutes to evaporate the solvent and thermally imidize it to obtain a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0502] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0503] (Manufacturing of polyimide film (post-baked polyimide film))
[0504] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0505] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0506] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0507] Comparative Example 7
[0508] In Example 10, except that the first inorganic film was not laminated, the same procedure as in Example 10 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0509] Table 3 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0510] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0511] Embodiment 11
[0512] (Manufacture of polyamic acid varnish)
[0513] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 39.434 g (0.100 mol) of diamine (b12) and 312.147 g of NMP were added, and the mixture was stirred at a temperature of 70° C. in the system under a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0514] To this solution, 29.422 g (0.100 mol) of s-BPDA and 78.037 g of NMP were added all at once, and the solution was stirred for 5 hours while being maintained at 70° C. with a heating mantle.
[0515] Then, 229.520 g of NMP was added, and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining a polyamic acid varnish having a solid content concentration of 10% by mass.
[0516] (Manufacturing of Laminated Body)
[0517] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0518] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 430°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heated at 430°C in a hot air dryer for 60 minutes to evaporate the solvent, thereby obtaining a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0519] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) composed of a supporting substrate, a first inorganic film, a polyimide resin and a second inorganic film.
[0520] (Manufacturing of polyimide film (post-baked polyimide film))
[0521] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0522] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0523] Table 4 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0524] Comparative Example 8
[0525] In Example 11, except that the first inorganic film was not laminated, the same procedure as in Example 11 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0526] Table 4 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0527] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0528] Example 12
[0529] (Manufacture of polyamic acid varnish)
[0530] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 46.333 g (0.100 mol) of diamine (b13) and 85.856 g of NMP were added, and the mixture was stirred at a temperature of 70° C. in the system under a nitrogen atmosphere at a rotation speed of 200 rpm to obtain a solution.
[0531] To this solution, 29.422 g (0.100 mol) of s-BPDA and 85.856 g of NMP were added all at once, and the mixture was stirred for 5 hours while being maintained at 70° C. with a heating mantle.
[0532] Then, 152.517 g of NMP was added, and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining a polyamic acid varnish having a solid content concentration of 10% by mass.
[0533] (Manufacturing of Laminated Body)
[0534] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0535] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 430°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heated at 430°C in a hot air dryer for 60 minutes to evaporate the solvent, thereby obtaining a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0536] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) formed by a supporting substrate, a first inorganic film, a polyimide resin, and a second inorganic film.
[0537] (Manufacturing of polyimide film (post-baked polyimide film))
[0538] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0539] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0540] Table 4 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0541] Comparative Example 9
[0542] In Example 12, except that the first inorganic film was not laminated, the same procedure as in Example 12 was carried out to obtain a laminate (support substrate / polyimide resin / second inorganic film) and a polyimide film (post-baked polyimide film).
[0543] Table 4 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0544] In addition, the supporting base material was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick).
[0545] Comparative Example 10
[0546] (Manufacture of polyamic acid varnish)
[0547] In a 1 L 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet pipe, a Dean-Stark apparatus equipped with a cooling tube, a thermometer, and a glass end cap, 32.024 g (0.100 mol) of TFMB and 196.627 g of NMP were added, and stirred at a rotation speed of 200 rpm at an internal temperature of 50° C. in a nitrogen atmosphere to obtain a solution.
[0548] To this solution, 29.422 g (0.100 mol) of s-BPDA and 49.157 g of NMP were added all at once, and the mixture was stirred for 5 hours while being maintained at 50° C. with a heating mantle.
[0549] Then, 307.230 g of NMP was added, and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining a polyamic acid varnish having a solid content concentration of 10% by mass.
[0550] (Manufacturing of Laminated Body)
[0551] On a supporting base material which was a glass substrate (AN-100, manufactured by AGC Corporation, 0.7 mm thick), a film with a thickness of 1000 mm was formed by sputtering. The SiO2 film serves as the first inorganic film.
[0552] The polyimide varnish is applied to the surface of a glass supporting substrate laminated with a SiO2 film as the first inorganic film, maintained at 80°C on a heating plate for 20 minutes, then heated to 400°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heated at 400°C in a hot air dryer for 60 minutes to evaporate the solvent and thermally imidize it to obtain a three-layer preliminary laminate (supporting substrate / first inorganic film / polyimide resin) formed by a supporting substrate, a first inorganic film, and a polyimide resin.
[0553] Next, a laminate (support substrate / first inorganic film / polyimide resin / second inorganic film) was manufactured by imitating the manufacturing process of a display for an image display device. Specifically, a sputtering film was formed on the polyimide resin side of the three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) obtained by the above method to a thickness of 1000 nm. A SiO2 film is used as the second inorganic film to obtain a stacked body (support substrate / first inorganic film / polyimide resin / second inorganic film) composed of a supporting substrate, a first inorganic film, a polyimide resin and a second inorganic film.
[0554] (Manufacturing of polyimide film (post-baked polyimide film))
[0555] By the above method, a three-layer preliminary laminate (support substrate / first inorganic film / polyimide resin) was obtained.
[0556] Next, the first inorganic film is peeled off from the interface between the first inorganic film and the polyimide resin to obtain a polyimide film (post-baked polyimide film).
[0557] Table 4 shows the physical properties and evaluation results of the polyimide film (polyimide film after post-baking) and the evaluation results of the laminate.
[0558] [Table 1]
[0559] Table 1
[0560]
[0561] (*1) The numbers in the polyimide resin column indicate the molar ratio of each component.
[0562] [Table 2]
[0563] Table 2
[0564]
[0565] (*1) The numbers in the polyimide resin column indicate the molar ratio of each component.
[0566] [Table 3]
[0567] Table 3
[0568]
[0569] (*1) The numbers in the polyimide resin column indicate the molar ratio of each component
[0570] [Table 4]
[0571] Table 4
[0572]
[0573] (*1) The numbers in the polyimide resin column indicate the molar ratio of each component.
[0574] As shown in Tables 1 to 4, the laminate of the present invention has excellent heat resistance, low yellowness, and small change in yellowness after heat treatment. The laminate of the present invention has excellent properties as described above and is therefore useful as a laminate for manufacturing a TFT substrate.
Claims
1. A laminate for manufacturing a TFT substrate, comprising: a glass support substrate, a first inorganic film laminated on the support substrate, a polyimide resin laminated on the first inorganic film, and a second inorganic film laminated on the polyimide resin, The polyimide resin has a structural unit of the following general formula (1) or a structural unit of the following general formula (2), and has a glass transition temperature of 400° C. or higher. In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group; R 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group; h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4; n is 0, 1 or 2; In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene; m is 0, 1 or 2; In formula (3), each R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.
2. The laminate according to claim 1, wherein The thickness of the first inorganic film is 1 to 1,000 nm, and the thickness of the second inorganic film is 1 to 1,000 nm.
3. The laminate according to claim 1, wherein At least one of the first inorganic film and the second inorganic film includes silicon.
4. The laminate according to claim 1, wherein The first inorganic film and the second inorganic film include at least one selected from silicon oxide, silicon nitride, and amorphous silicon.
5. A method for producing a laminate, comprising: A step of applying a varnish containing a polyimide resin and an organic solvent on a glass support substrate and a first inorganic film laminated on the support substrate, and heating the varnish at 400° C. or higher; and a step of laminating a second inorganic film, The polyimide resin has a structural unit of the following general formula (1) or a structural unit of the following general formula (2), In formula (1), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group; R 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group; h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4; n is 0, 1 or 2; In formula (2), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and fluorenylene; m is 0, 1 or 2; In formula (3), each R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.
6. A method for producing a laminate, comprising: A step of applying a varnish containing a polyimide resin precursor and an organic solvent on a glass support substrate and a first inorganic film laminated on the support substrate, and heating the varnish at 400° C. or higher; and a step of laminating a second inorganic film, The polyimide resin precursor has a structural unit of the following general formula (4) or a structural unit of the following general formula (5), In formula (4), X 1 is a tetravalent group having an alicyclic structure or an aromatic ring, Y 1 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group; R 1 , R 2 Each independently represents a methyl group, a fluoro group or a trifluoromethyl group; R 3 , R 4 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms; h and i are integers of 0 to 4, at least one of which is an integer of 1 to 4; n is 0, 1 or 2; In formula (5), X 2 Contains a tetravalent group represented by the following general formula (3), Y 2 is at least one selected from the group consisting of a single bond, -NHCO-, -CONH-, -COO-, -OCO- and a fluorenylene group; R 5 , R 6 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms; m is 0, 1 or 2; In formula (3), each R is independently a methyl group, a fluoro group or a trifluoromethyl group, p is an integer of 1 to 4, and k is 1 or 2.
7. A method for producing a laminate for a TFT substrate, wherein: A TFT functional layer is stacked on the second inorganic film in the laminate according to any one of claims 1 to 4, and the first inorganic film is peeled off from the interface with the polyimide resin. 8 . A laminate for a TFT substrate, obtained by the production method according to claim 7 . 9 . An electronic device comprising the laminate for a TFT substrate according to claim 8 .
Citation Information
Patent Citations
Polymers for use in electronic devices
JP2022530104A
